ANALISIS NERACA AIR SUB DAS KAMPAR KANAN - Reno Diah Putri; Manyuk Fauzi; Gunawan Wibisono (LPPM Universitas Abdurrab, 2025)
Kampar Kanan Watershed is a supporter of community activities so that its sustainability needs to be considered and managed optimally. One effort that can be made in monitoring water availability is to analyze the water balance. This study aims to analyze the condition of the water balance in the Kampar Kanan Watershed based on all rainy season scenarios to prevent water shortage conditions in all rainy season scenarios. The method used to calculate water availability in this study is the regional method. Based on the results of the water balance analysis, the water availability of the Kampar Kanan Watershed is able to meet all water needs. However, there are several intake nodes that experience deficits, namely Node 11 Node 12 and Node 15